The global semiconductor shortage crisis – Why the high demand isn’t met by supply, a sign of a bigger crisis or a standalone issue? : - Bok, Martin (2022)
The global semiconductor shortage became the most prominent part of the worldwide supply chain crisis that has shaken the world together with the COVID-19 pandemic. This is because the importance of semiconductors has never been greater as new cars, phones, graphic cards, processing units, and other common-end products of the 21st century require an ever-increasing number of semiconductors to work correctly. this thesis explores whether the shortage would have occurred without the COVID-19 pandemic and whether the causes of this crisis will lead to similar global supply shocks for other industries. The thesis also aims to give recommendations on how to best solve this crisis and assess if the global reaction to the crisis was sufficient and well-aimed. The methodology used to conclude the answer is comparative work synthesizing shattered and still evolving secondary literature on the ongoing crisis with the primary sources of other, relevant research. The findings suggest that the COVID-19 wasn’t the primary cause of the semiconductor shortage, it was a catalyst for it. The core causes of the semiconductor shortage are intertwined with the complex nature of the semiconductor products. The thesis offers three recommendations for the semiconductor industry. Overall, the global reaction to the crisis has been mostly well targeted but it is very unlikely that the semiconductor shortage will be resolved before 2024.